Removal of toxic and alkali/alkaline earth metals during co-thermal treatment of two types of MSWI fly ashes in China. (December 2015) - Yu, Jie; Qiao, Yu; Jin, Limei; Ma, Chuan; Paterson, Nigel; Sun, Lushi
Graphical abstract: Highlights: Most alkali/alkaline earth metals could be removed. Cd and Pb can be nearly completely removed under all conditions. Alkali/alkaline earth metals can promote removal of Cu by formation of CuCl2 . The removal of Zn and Cr was low due to formation of stable compounds. Removal of Zn was accelerated and Cu was hindered in N2 . Abstract: This study aims to vaporize heavy metals and alkali/alkaline earth metals from two different types of fly ashes by thermal treatment method. Fly ash from a fluidized bed incinerator (HK fly ash) was mixed with one from a grate incinerator (HS fly ash) in various proportions and thermally treated under different temperatures. The melting of HS fly ash was avoided when treated with HK fly ash. Alkali/alkaline earth metals in HS fly ash served as Cl-donors to promote the vaporization of heavy metals during thermal treatment. With temperature increasing from 800 to 900 °C, significant amounts of Cl, Na and K were vaporized. Up to 1000 °C in air, less than 3% of Cl and Na and less than 5% of K were retained in ash. Under all conditions, Cd can be vaporized effectively. The vaporization of Pb was mildly improved when treated with HS fly ash, while the effect became less pronounced above 900 °C. Alkali/alkaline earth metals can promote Cu vaporization by forming copper chlorides. Comparatively, Zn vaporization was low and only slightly improved by HS fly ash. The low vaporization of Zn could be caused by the formation of Zn2 SiO4, ZnFe2 O4 and ZnAl2 O4 . Under all conditions, less than 20% of Cr was vaporized. In a reductive atmosphere, the vaporization of Cd and Pb were as high as that in oxidative atmosphere. However, the vaporization of Zn was accelerated and that of Cu was hindered because the formation of Zn2 SiO4, ZnFe2 O4 and ZnAl2 O4 and copper chloride was depressed in reductive atmosphere.